The Effects of Cost Containment and Price Policies on Pharmaceutical Expenditure in South Korea - Woohyeon Kim; Heejo Koo; Hye-Jae Lee; Euna Han (Kerman University of Medical Sciences, 2022)
Background  Policy-makers have proposed and implemented various cost-containment policies for drug prices and quantities to regulate rising pharmaceutical spending. Our study focused on a major change in pricing policy and several incentive schemes for curbing pharmaceutical expenditure growth during the 2010s in Korea. Methods  We constructed the longitudinal dataset from 2008-2017 for 12 904 clinics to track the prescriber behavior before and after the implemented policies. Applying an interrupted time series model, we analyzed changes in trends in overall monthly drug expenditure and antibiotic drug expenditure per prescription for outpatient claims diagnosed with three major diseases before and after the policies' implementation. Results  Significant price reductions and incentives for more efficient drug prescriptions resulted in an immediate decrease in monthly drug expenditures in clinics. However, we found attenuated effects over the long run. The topspending clinics showed the highest rate of increase in drug costs. Conclusion  Future policy interventions can maximize their effects by targeting high-spending providers.